Continuous intergenerational play for neuroplasticity - Pišot, Rado (Annales kinesiologiae (Koper), 2025)
This case study compared the acute effects of high-intensity interval training (HIIT) and moderate-intensity continuous training (MICT) on vascular and microva-scular function in a healthy male subject (age: 34 yrs; body mass index: 25.82 kg/m2). Key vascular parameters were assessed, including augmentation index (AIx), ca-rotid-femoral and brachial-ankle pulse wave velocity (cfPWV, baPWV), flow-mediated slowing (FMS%), and tissue saturation index (TSI) recovery slope. HIIT induced a greater reduction in baPWV (mean difference MD: 0.9 m/s) and a higher increase in FMS% (MD: 8%) compared to MICT, indicating more favourable changes in periphe-ral arterial stiffness and endothelial function. Additionally, the reoxygenation slope for TSI was more pronounced after HIIT, suggesting improved microvascular recove-ry. Interestingly, AIx increased following MICT (MD from baseline: 11%) but slightly decreased after HIIT (MD from baseline: -5%). These findings suggest that exercise intensity plays a critical role in determining vascular adaptations, with HIIT showing superior acute benefits
Keywords: gibalno-kognitivne vaje; lateralni motorični proces; nevrološki razvoj; nevroplastičnost; spodbujanje zdravja; Šport